CircIL4R facilitates the tumorigenesis and inhibits ferroptosis in hepatocellular carcinoma by regulating the miR‐541‐3p/GPX4 axis. (31st August 2020) - Xu, Qinhong; Zhou, Lijing; Yang, Ganghua; Meng, Fandi; Wan, Yong; Wang, Lin; Zhang, Lei
Abstract: Ferroptosis is a specific iron‐dependent cell death form that can induce the production of lipid peroxide, but the roles of circular RNAs (circRNAs) in ferroptosis are completely unaware. Circ‐interleukin‐4 receptor (circIL4R) was reported to express highly in hepatocellular carcinoma (HCC). This study focused on the function of circIL4R dysregulation in tumor progression and ferroptosis of HCC, as well as its molecular mechanism. The quantitative real‐time polymerase chain reaction was implemented for measuring RNA expression. Cell proliferation and survival were evaluated using 3‐(4, 5‐dimethylthiazol‐2‐y1)‐2, 5‐diphenyl tetrazolium bromide. Apoptotic cells were detected via flow cytometry. The quantification of protein expression was executed through western blotting analysis. The target binding was assessed via the dual‐luciferase reporter, RNA immunoprecipitation, and RNA pull‐down assays. The experiment in vivo was performed using a xenograft model. CircIL4R was abnormally overexpressed in HCC tissues and cells. CircIL4R knockdown impeded oncogenesis and expedited ferroptosis of HCC cells. CircIL4R could directly sponge microRNA‐541‐3p (miR‐541‐3p) and miR‐541‐3p inhibition mitigated the effects of circIL4R knockdown on HCC cells. CircIL4R acted as a miR‐541‐3p sponge to regulate its target glutathione peroxidase 4 (GPX4). GPX4 upregulation relieved the miR‐541‐3p‐induced tumor inhibition and ferroptosis aggravation. CircIL4R played an oncogenic role in HCC via the miR‐541‐3p/GPX4 axis in vivo. Our data suggested that circIL4R served for a tumor promoter and ferroptosis inhibitor in HCC by the miR‐541‐3p/GPX4 network.